Promoting parent-child relationships and preventing violence via home-visiting: a pre-post cluster randomised trial among Rwandan families linked to social protection programmes - Theresa S. Betancourt; Sarah K. G. Jensen; Dale A. Barnhart; Robert T. Brennan; Shauna M. Murray; Aisha K. Yousafzai; Jordan Farrar; Kalisa Godfroid; Stephanie M. Bazubagira; Laura B. Rawlings; Briana Wilson; Vincent Sezibera; et al. (BMC, 2020)
Abstract Background Sugira Muryango is a father-engaged early child development and violence-prevention home-visiting programme delivered by trained lay workers. This cluster-randomised trial evaluates whether families living in extreme poverty (Ubudehe 1, the poorest category in the Government of Rwanda's wealth ranking) who receive Sugira Muryango in combination with a government-provided social protection programme demonstrate greater responsive, positive caregiving, nutrition, care seeking, hygiene, and father involvement compared with control families receiving usual care (UC). Methods Using detailed maps, we grouped closely spaced villages into 284 geographic clusters stratified by the type of social protection programmes operating in the village clusters; 198 clusters met all enrolment criteria. Sugira Muryango was delivered to n = 541 families in 100 treatment clusters with children aged 6-36 months living in extreme poverty. We assessed changes in outcomes in intervention and n = 508 UC control families using structured surveys and observation. Analyses were intent to treat using mixed models to accommodate clustering. Results Families receiving Sugira Muryango improved on core outcomes of parent-child relationships assessed using the Home Observation for Measurement of the Environment (Cohen's d = 0.87, 95% CI: 0.74, 0.99) and the Observation of Mother-Child Interaction (Cohen's d = 0.29, 95% CI: 0.17, 0.41). We also saw reductions in harsh discipline on items from the UNICEF MICS (OR = 0.30: 95% CI: 0.19, 0.47) and in violent victimisation of female caregivers by their partners (OR = 0.49, 95% CI: 0.24, 1.00) compared with UC. Moreover, children in families receiving SM had a 0.45 higher increase in food groups consumed in the past 24 h (Cohen's d = 0.35, 95% CI: 0.22, 0.47), increased care seeking for diarrhoea (OR = 4.43, 95% CI: 1.95, 10.10) and fever (OR = 3.28, 95% CI: 1.82, 5.89), and improved hygiene behaviours such as proper treatment of water (OR = 3.39, 95% CI: 2.16, 5.30) compared with UC. Finally, Sugira Muryango was associated with decreased caregiver depression and anxiety (OR = 0.58, 95% CI: 0.38, 0.88). Conclusions Sugira Muryango led to improvements in caregiver behaviours linked to child development and health as well as reductions in violence. Trial registration ClinicalTrials.gov number NCT02510313 .